Optimization of conditions for microclonal propagation of SALVIA PRATENSIS L. - Buchenkov I.E.; Lemiasheuski V.O.; Sysa A.G.; Xin Sui; Liu Yang; Zengyi Song (BIO Web of Conferences)
The possibility of introducing Salvia pratensis, a protected medicinal plant of the Republic of Belarus, into in vitro culture for mass reproduction and return to natural ecosystems, as well as practical use as medicinal plant raw materials, has been studied. A sterilization regime for Salvia pratensis when introducing it into culture has been identified, which provides the best ratio of the number of sterile plant explants and the number of viable seeds. The optimal sterilizing agent is 0.1% silver nitrate solution with an exposure time of 20 minutes. The effect of various concentrations of gibberellic acid over a certain period of time on Salvia pratensis seeds has been identified. It has been established that a 10% solution of gibberellic acid for one hour has the greatest effect on seed germination for Salvia pratensis. Nutrient media have been selected for in vitro cultivation of Salvia pratensis plants. The optimal nutrient medium for Salvia pratensis is MR20.